Pb isotope insight into the formation of the Earth's first stable continents - Hartnady, Michael; Kirkland, Christopher; Smithies, R. Hugh; Johnson, S.P.; Johnson, Tim (ELSEVIER, 2022)
The formation of stable buoyant continental crust during the Archaean Eon was fundamental in establishing the planet's geochemical reservoirs. However, the processes that created Earth's first continents and the timescales over which they formed are debated. Here, we report the Pb isotope compositions of K-feldspar grains from 52 Paleoarchaean to Neoarchaean granites from the Pilbara Craton in Western Australia, one of the world's oldest and best-preserved granite–greenstone terranes. The Pb isotope composition of the Pilbara K-feldspars is variable, implying the granites were derived from crustal precursors of different age and/or variable time-integrated 238U/204Pb and 232Th/204Pb compositions. Trends to sub-mantle 207Pb/206Pb ratios preclude the influence of 4.3 Ga crustal precursors. In order to estimate crustal residence times we derive equations to calculate source model ages in a linearized Pb isotope evolution system. The best agreement between the feldspar Pb two-stage source model ages and those derived from zircon initial Hf isotope compositions requires crustal precursors that separated from a chondritic mantle source between 3.2 and 3.8 Ga, and rapidly differentiated to continental crust with 238U/204Pb and 232Th/238U ratios of ∼14 and 4.2–4.5, respectively. The preservation of Pb isotope variability in the Pilbara Paleoarchaean granites indicates their early continental source rocks were preserved for up to 500 Ma after their formation. The apparent longevity of these early continental nuclei is consistent with the incipient development of buoyant melt-depleted cratonic lithosphere during the Eoarchaean to Paleoarchaean.